2021
DOI: 10.1002/cbdv.202100735
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Characterization of a Novel Plant Carotenoid Cleavage Dioxygenase 1 from Morus notabilis

Abstract: Synthesis of β-ionone in microbial cell factories is limited by the efficiency of carotenoid cleavage dioxygenases (CCDs). To obtain genes responsible for specific cleavage of carotenoids generating β-ionone, a novel carotenoid cleavage dioxygenase 1 from Morus notabilis was cloned and overexpressed in Escherichia coli. The MnCCD1 protein was able to cleave a variety of carotenoids at the positions 9, 10 (9', 10') to produce βionone, 3-hydroxy-4-oxo-β-ionone, 3-hydroxy-β-ionone, and 3-hydroxy-α-ionone in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In order to obtain CCD1 that are more compatible with the C. tropicalis expression system, we investigated different CCD1 from Petunia hybrida, Morus notabilis, and Helianthus annuus (PhCCD1, MnCCD1 and HaCCD1 to optimize β-ionone synthesis in C. tropicalis.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain CCD1 that are more compatible with the C. tropicalis expression system, we investigated different CCD1 from Petunia hybrida, Morus notabilis, and Helianthus annuus (PhCCD1, MnCCD1 and HaCCD1 to optimize β-ionone synthesis in C. tropicalis.…”
Section: Resultsmentioning
confidence: 99%
“…The possible explanation was the volatile ability of products was too low or the products were catabolized by the strains ( Auldridge et al, 2006b ). Previous studies have shown that CCD1 can cleave the substrates at the 9, 10 (9′, 10′) bond sites, such as CCD1 from A. thaliana ( Schwartz et al, 2001 ), tea plant ( Wang et al, 2020a ), Morus notabilis ( Qi et al, 2021 ), Petunia hybrida ( Simkin et al, 2004b ), Lycopersicon esculentum ( Simkin et al, 2004a ), Rosa damascena ( Huang et al, 2009 ), Osmanthus fragrans ( Baldermann et al, 2010 ). When beta-carotene was the substrate for CCD1, the cleavage at the 9, 10 (9′, 10′) bond sites can produce beta-ionone ( Schwartz et al, 2001 ), which can influence the fragrance and flavors of flowers, fruits, and essential oils ( Schwartz et al, 2001 ; Simkin et al, 2004a , b ; Brandi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other CCD1 enzymes from Arabidopsis, Bixa Orellana, Zea mays , and Lycopersicon esculentum can also cleave lycopene at 5, 6 and/or 5′, 6′ bond sites to form MHO ( Vogel et al, 2008 ). However, MnCCD1 failed to produce MHO but produced pseudoionone due to the cleavage at 9, 10 (9′, 10′) sites ( Qi et al, 2021 ). CCD1 from carrot didn’t use lycopene as a substrate ( Yahyaa et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Fe 2+ ion seems not to be an essential constituent in CCD1's reaction mix for in vitro characterization. 44,45 Additionally, other metal ions show no obvious regularity on CCD1. It has been reported that most metal ions showed a slight enhancement effect on the activity of MnCCD1 and HaCCD1, while a significant inhibitory effect was observed on PhCCD1.…”
Section: Characterization Of Ccd1mentioning
confidence: 98%